2017
DOI: 10.1007/s00586-017-5009-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-piece ALIF cage optimizes the bone–implant interface in a 360° setting

Abstract: Introduction Clinical research has documented that cage subsidence and the loss of balance correction is a significant complication related to spinal fusion. Subsidence is a multifactorial complication, where implant design is one important element. The aim of the study is to compare the rigidity and bone-implant relative motion of segments treated with either a conventional one-piece ALIF cage versus a two-piece ALIF cage, which adapts in situ and permits 7°-21°of lordosis. Methods Seven lumbosacral (L3-S1) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…These designs have demonstrated more robust angular correction in cadavers. 156 Well-designed clinical trials and comparisons of the rapidly developing new designs have not yet been performed. 112…”
Section: Structural and Engineering Developments In Devices For Antermentioning
confidence: 99%
“…These designs have demonstrated more robust angular correction in cadavers. 156 Well-designed clinical trials and comparisons of the rapidly developing new designs have not yet been performed. 112…”
Section: Structural and Engineering Developments In Devices For Antermentioning
confidence: 99%
“…For example, it has been reported that cages with sharp teeth design have greater pull-out forces [9]. In an effort to optimize and evaluate the stability of ALIF cages, several studies have described the biomechanical results of different ALIF cage designs [9][10][11][12]. However, the detailed features of the resistance against static expulsion of ALIF cages are not yet known [13].…”
Section: Introductionmentioning
confidence: 99%